Piezoelectric and dielectric properties of electrospun polyvinylidene fluoride (PVDF) blended with cellulose nanocrystals (CNCs) - Aminatul Sobirah, Zahari; Muhammad Hafiz, Mazwir; Izan Izwan, Misnon; Farah Hanani, Zulkiﬂi; Mohammad Haﬁzuddin, Hj Jumali; Nor Huwaida Janil, Jamil (John Wiley & Sons, Inc., 2025)
PVDF is a semicrystalline polymer made up of repeating units of ─CH2CF2─ monomer and has five crystalline phases, which are α, β, γ, δ, and ε-phases. However, piezoelectricity of PVDF is dependent on the β-phase crystalline. Thus, to increase the formation of the β-phase, CNCs with various weights (1%–5%) are incorporated into PVDF by using the electrospinning method. The influence of CNCs on electrospun PVDF/CNCs is investigated by using analytical methods such as FESEM, FTIR, XRD, universal testing machine (UTM), electrochemical impedance spectroscopy (EIS), and piezoelectric d33 meter. After incorporating CNCs into electrospun PVDF, two peaks of α-phase diminished in FTIR absorption and the addition also enhanced mechanical and dielectric properties of the membrane. The piezoelectric constant, dielectric properties, and β-phase content also increased with higher CNCs addition. PVDF with 4% CNCs has the highest β-phase content up to 91.74% with the maximum piezoelectric constant, d33 of 45.0 pCN−1 and dielectric constant of 5.4.